2016
DOI: 10.1016/j.bjm.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of polynuclear aromatic hydrocarbons by two strains of Pseudomonas

Abstract: The goal of this investigation was to isolate competent polynuclear aromatic hydrocarbons degraders that can utilize polynuclear aromatic hydrocarbons of former industrial sites at McDoel Switchyard in Bloomington, Indiana. Using conventional enrichment method based on soil slurry, we isolated, screened and purified two bacterial species strains PB1 and PB2. Applying the ribotyping technique using the 16S rRNA gene analysis, the strains were assigned to the genus Pseudomonas (Pseudomonas plecoglossicida strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…There are very fewer reports of chrysene degradation in microcosms. Nwinyi et al (2016) observed 14 to 15% degradation of chrysene in 2–3 weeks in laboratory media having a final concentration of 64 mg/kg. But degradation was not examined in microcosm or soil.…”
Section: Resultsmentioning
confidence: 96%
“…There are very fewer reports of chrysene degradation in microcosms. Nwinyi et al (2016) observed 14 to 15% degradation of chrysene in 2–3 weeks in laboratory media having a final concentration of 64 mg/kg. But degradation was not examined in microcosm or soil.…”
Section: Resultsmentioning
confidence: 96%
“…DNA was screened for eight different beta-lactamase genes, including ESBLs (SHV, TEM and CTX-M genes), Oxacillinase (OXA) and carbapenemases (IMP, VIM, KPC and NDM genes). Beta-lactamase genes were screened for using specific primers (Table 3) as previously described [55][56][57][58]. For polymerase chain reaction (PCR) amplification of beta-lactamase genes in a thermocycler C100 Touch (Bio-RAD, USA), 5 µL aliquot of DNA template was added to a 20 µL master mix.…”
Section: Dna Extraction and Genotypic Detection Of β-Lactamase Genesmentioning
confidence: 99%
“…The high incidence of Pseudomonas species in naphthalene enrichments, as well as their PAH biodegradation ability, has been widely reported (Amini et al 2017;Nwinyi et al 2016;Thomas et al 2016;Patowary et al 2015;Wald et al 2015;Ma et al 2012;Obayori et al 2008;Ma et al 2006;Leahy and Colwell 1990;Foght and Westlake 1988). However, this is the first study reporting the naphthalene biodegradation ability of P. silesiensis, P. arsenicoxydans, P. umsongensis, P. laurylsulfatiphila, P. mandelii, and P. laurentiana; so far, no other PAH compound degradation ability of isolates affiliated with these species has been reported either.…”
Section: Discussionmentioning
confidence: 81%